쑥 (Artemisia princeps P.) 추출물이 고지방식이를 급여한 흰쥐의 대사장애 및 아디포카인 조절에 미치는 영향 - 김윤혜(Kim, Yun-Hye); 박충무(Park, Chung-Mu); 윤군애(Yoon, Gun-Ae) (Journal of nutrition and health, 2016)
Purpose: Dysregulation of adipokines caused by excess adipose tissue has been implicated in the development of obesity-related metabolic diseases. This study evaluated the effects of mugwort (Artemisia princeps Pampanini) ethanol extract on lipid metabolic changes, insulin resistance, adipokine balance, and body fat reduction in obese rats. Methods: Male Sprague-Dawley rats were fed either a control diet (NC), high-fat diet (HF, 40% kcal from fat), or high-fat diet with 1% mugwort extract (HFM) for 6 weeks. Results: Epididymal and retroperitoneal fat mass increased in the HF group compared with the NC group, and epididymal fat mass was reduced in the HFM group (p < 0.05). No difference was observed in serum levels of total cholesterol (TC) and high-density lipoprotein cholesterol (HDL-C) among the groups. However, triglyceride (TG), TG/HDL-C ratio, and TC/HDL-C ratio increased in the HF group and significantly decreased in the HFM group. TG and TC levels in the liver were significantly higher in the HF group, whereas these levels were significantly reduced in the HFM group. HF rats had lower insulin sensitivity as indicated by increased homeostasis model assessment of the insulin resistance (HOMA-IR) value. HOMA-IR values significantly decreased in the HFM group. Adiponectin levels were higher in NC rats, and their leptin and PAI-1 levels were lower. Relative balance of adipokines was reversed in the HF group, with lower adiponectin levels but higher leptin and PAI-1 levels. In contrast, the HFM group maintained balance of adiponectin/leptin and adiponectin/PAI-1 levels similar to NC by reducing leptin and PAI-1 levels. Conclusion: Overall data indicated that mugwort extract can be effective in alleviating metabolic dislipidemia, insulin resistance, and adipokine dysregulation induced by a high-fat diet. 본 연구는 고지방식이와 쑥추출물이 흰쥐의 지질대사, 인슐린저항성, 아디포카인 분비에 미치는 효과를 측정하였다. 고지방식이에 의해 부고환지방과 복막후강지방의 축적이 증가되었고, 그 결과 혈장 항염증성 아디포카인은 감소하고 염증성 아디포카인은 증가하여 아디포넥틴/렙틴 및 아디포넥틴/PAI-1 비가 저하되는 불균형을 초래하였다. 내장지방 축적과 관련된 아디포카인의 불균형은 TG, TG/HDL-C, TC/HDL-C를 증가시키고 HOMA-IR의 증가를 유발한 것으로 추정된다. 이에 비해 쑥 에탄올추출물의 첨가는 부고환지방과 복막후강지방의 축적을 완화함으로써 PAI-1과 렙틴을 감소시켜 아디포넥틴/렙틴 및 아디포넥틴/PAI-1 비의 저하를 억제하고 아디포카인의 균형을 상대적으로 유지하였으며, TG, TG/HDL-C, TC/HDL-C 및 HOMA-IR 수치가 감소하였다. 따라서 쑥 에탄올추출물은 내장지방 축적을 억제하고 아디포카인의 분비, 특히 염증성물질인 렙틴과 PAI-1의 분비를 저하시켜 아디포카인의 균형을 조절함으로써 지질대사 및 인슐린저항성을 개선하는 효과가 있는 것으로 나타났다.